STRATEGY MANAGEMENT OF TEACHER EXAMPLE IN FORMING CHILDREN'S MORAL RELIGIOUS VALUES - Suzana, Suzana; Julaekha, Siti; Sulaiman, Sulaiman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Moral values are the good and bad of a persons behavior, especially early childhood. Behavior can be influenced by the surrounding environment, such as the family and school environment. Educators act as models for children to provide exemplary examples to young children to create good words and behavior. The aim of this research is to find out the picture of exemplary religious morals such as children saying hello, shaking hands with teachers when they meet, being honest and keeping the environment clean. Qualitative research method with a research focus on implementing teacher example in forming moral and religious values in early childhood. Data collection techniques use observation, interviews and documentation, with primary data sources namely schools, class teachers and parents. Secondary data sources are references from various books related to religious morals and role models. The results of the research show that instilling religious and moral values through teaching and learning activities is very effective. The findings in this research show that the process of instilling religious and moral values through teacher example can shape children to know and be grateful for God creation, carry out daily worship, maintain personal and environmental cleanliness, recognize religious holidays, behave politely and honestly, and helping parents, educators and friends